Effects of an artificial hay aroma and compound feed formulation on feed intake pattern, rumen function and milk production in lactating dairy cows. (3rd October 2019) - Abd Rahim, S.; van Laar, H.; Dijkstra, J.; Navarro-Villa, A.; Fowers, R.; Hendriks, W. H.; Pellikaan, W. F.; Leen, F.; Martín-Tereso, J.
Abstract : The Kempen system is a dairy feeding system in which diet is provided in the form of a compound feed (CF ) and hay offered ad libitum . Ad libitum access to CF and hay allows cows in this system to achieve a high DM intake (DMI ). Out of physiological concerns, the voluntary hay intake could be increased and the consumption pattern of CF could be manipulated to maintain proper rumen functioning and health. This study investigated the effects of an artificial hay aroma and CF formulation on feed intake pattern, rumen function and milk production in mid- to late-lactating dairy cows. Twenty Holstein–Friesian cows were assigned to four treatments in a 4 × 4 Latin square design. Diet consisted of CF and grass hay (GH ), fed separately, and both offered ad libitum, although CF supply was restricted in maximum meal size and speed of supply by an electronic system. Treatments were the combination of two CF formulations – high in starch (CHS ) and fibre (CHF ); and two GH – untreated (UGH ) and the same hay treated with an artificial aroma (TGH ). Meal criteria were determined using three-population Gaussian–Gaussian–Weibull density functions. No GH × CF interaction effects on feed intake pattern characteristics were found. Total DMI and CF intake, but not GH intake, were greater ( P < 0.01) in TGH treatment, and feed intake was not affected by type of CF. Total visits to feeders per day, visits to the GH feeder, visits to the CF feeder and CF eating time (all P < 0.01) were significantly greater in cows fed with TGH. Meal frequency, meal size and meal duration were unaffected by treatments. Cows fed CHF had a greater milk fat ( P = 0.02), milk urea content ( P < 0.01) and a greater milk fat yield ( P < 0.01). Cows fed TGH had a greater milk lactose content and lactose yield ( P < 0.05), and milk urea content ( P < 0.01). Cows fed TGH had smaller molar proportions of acetic acid and greater molar proportions of propionic acid compared with UGH. In conclusion, treatment of GH with an artificial aroma increased CF intake and total DMI, but did not affect hay intake. Additionally, GH treatment increased the frequency of visits to both feeders, and affected rumen volatile fatty acid profile. Type of CF did not affect meal patterns, ruminal pH, nor fermentation profiles.